Study of the material photon and electron background and the liquid argon detector veto efficiency of the CDEX-10 experiment*Supported by National Natural Science Foundation of China (11175099, 10935005, 10945002, 11275107, 11105076) and State Key Development Program of Basic Research of China (2010CB833006). (March 2015) - Su 苏, Jian 健; Zeng 曾, Zhi 志; Ma 马, Hao 豪; Yue 岳, Qian 骞; Cheng 程, Jian-Ping 建平; Chang 常, Jian-Ping 建平; Chen 陈, Nan 楠; Chen 陈, Ning 宁; Chen 陈, Qing-Hao 庆豪; Chen 陈, Yun-Hua 云华; Chuang 庄, Yo-Chun 又澄; Deng 邓, Zhi 智; et al.
Abstract: The China Dark Matter Experiment (CDEX) is located at the China Jinping Underground Laboratory (CJPL) and aims to directly detect the weakly interacting massive particles (WIMP) flux with high sensitivity in the low mass region. Here we present a study of the predicted photon and electron backgrounds including the background contribution of the structure materials of the germanium detector, the passive shielding materials, and the intrinsic radioactivity of the liquid argon that serves as an anti-Compton active shielding detector. A detailed geometry is modeled and the background contribution has been simulated based on the measured radioactivities of all possible components within the GEANT4 program. Then the photon and electron background level in the energy region of interest (<10 −2 events·kg 1 ·day −1 ·keV −1 (cpkkd)) is predicted based on Monte Carlo simulations. The simulated result is consistent with the design goal of the CDEX-10 experiment, 0.1cpkkd, which shows that the active and passive shield design of CDEX-10 is effective and feasible.